Association between metformin prescription and growth rates of abdominal aortic aneurysms. Issue 11 (26th June 2017) - Golledge, J; Moxon, J; Pinchbeck, J; Anderson, G; Rowbotham, S; Jenkins, J; Bourke, M; Bourke, B; Dear, A; Buckenham, T; Jones, R; Norman, P E
Abstract: Background: It has been suggested that diabetes medications, such as metformin, may have effects that inhibit abdominal aortic aneurysm (AAA) growth. The aim of this study was to examine the association of diabetes treatments with AAA growth in three patient cohorts. Methods: AAA growth was studied using ultrasound surveillance in cohort 1, repeated CT in cohort 2 and more detailed repeat CT in cohort 3. Growth was estimated by the mean annual increase in maximum AAA diameter. Results: A total of 1697 patients with an AAA were studied, of whom 118, 39 and 16 patients were prescribed metformin for the treatment of diabetes in cohorts 1, 2 and 3 respectively. Prescription of metformin was associated with a reduced likelihood of median or greater AAA growth in all three cohorts (cohort 1: adjusted odds ratio (OR) 0·59, 95 per cent c.i. 0·39 to 0·87, P = 0·008; cohort 2: adjusted OR 0·38, 0·18 to 0·80, P = 0·011; cohort 3: adjusted OR 0·13, 0·03 to 0·61, P = 0·010). No other diabetes treatment was significantly associated with AAA growth in any cohort. Conclusion: These findings suggest a potential role for metformin in limiting AAA growth. Abstract : Worth an RCT